Initiation of Prevention of Violence against Women and Children through Community-Based Resilience Strengthening in Pedak, Srandakan, Bantul - Merita Arini; R. Dirwan Suryo Soularto; Harumi Iring Primastuti (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2023)
Violence against women/children (VaW/C) has bio-psycho-socio-economic impacts. The Pedak community has not been exposed to efforts for violence prevention, although some VaW/C cases have arisen. Hence, this community service aimed to increase public awareness to prevent and reduce VaW/C. The approach Community-Based Resilience is carried out through a cycle of action research, including diagnosing, planning, action, and evaluation in Padukuhan Pedak, Trimurti, Srandakan, Bantul, Yogyakarta Province. Observation of the community conditions and in-depth interviews with community leaders were used in the diagnosing stage. The action stage includes three priority actions: VaW/C education for community representatives (a quasi-experiment), VaW/C education in children's reading corners, and youth Posyandu coaching. These activities increased public knowledge and reactivated community activities to prevent and overcome societal violence. Multisector role involvement and a multifaceted approach are needed to increase community awareness of VaW/C and assist them in designing applicable and sustainable programs.